Successful Myomectomy with Pregnancy - Khan, Kohinoor; Fatema, Kaniz; Ashraf, Manabi Binte; Patuary, Noor E Alam; Haldar, Harbilash (Journal of Bangladesh College of Physicians and Surgeons, 2020)
The prevalence of Leiomyomas with pregnancy is reported as 0.3-2.9%1.They usually remain asymptomatic during pregnancy, if they are small.In symptomatic one, management is generally expectant and surgical removal is particularly delayed until after delivery. Symptomatic myoma, which does not respond to conservative management need antenatal myomectomy. Second trimester is preferable for its better outcome8,12.We present a case of symptomatic multiple uterine fibroids which include a huge one, diagnosed during pregnancy clinically & ultrasonography confirmed it. The casewas managed successfully by antenatal myomectomy due to failure of conservative management.Totalweight of fibroids was 1500gms. The pregnancy progressed to term uneventfully & elective caesarian section was done on 28/04/2019 for transverse lie. A healthy female baby weighing 03Kg was delivered. The patient was discharged in good condition on 05/05/2019. J Bangladesh Coll Phys Surg 2021; 39(1): 59-61